2006
DOI: 10.1007/s10549-006-9279-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals an osteoblast-like phenotype for human osteotropic breast cancer cells

Abstract: Metastatic breast cancer cells exhibit the selective ability to seed and grow in the skeleton. We and others have previously reported that human breast tumors which metastasize to the skeleton overexpress bone matrix extracellular proteins. In an attempt to reveal the osteoblast-like phenotype of osteotropic breast cancer cells, we performed a microarray study on a model of breast cancer bone metastasis consisting of the MDA-MB-231 human cell line and its variant B02 selected for its high capacity to form bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 80 publications
8
79
0
4
Order By: Relevance
“…Interestingly, a number of proteins taking part either in bone mineralization or destruction were noticeable consistent with our 13 , and others' 16,17 , description of an osteoblast-like phenotype acquired by bone metastatic cells.…”
Section: Introductionsupporting
confidence: 92%
“…Interestingly, a number of proteins taking part either in bone mineralization or destruction were noticeable consistent with our 13 , and others' 16,17 , description of an osteoblast-like phenotype acquired by bone metastatic cells.…”
Section: Introductionsupporting
confidence: 92%
“…2 Using a similar approach in which bone-homing clones of MDA-MB-231 cells were compared with parental cells, we and others have found that bone homing is associated with decreased cellcell adhesion and migration, coupled with significantly reduced levels of the cell adhesion molecule fibronectin and calcium signal binding protein S100A4. 65,66 Interestingly, we also found a strong link between IL-1B expression and bone homing in both MDA-MB-231 cells and primary tumours from breast cancer patients, indicating that this molecule may promote an invasive and motile phenotype in breast cancer cells. 66 In fitting agreement with the hypothesis that breast cancer cells acquire genotypic similarities to cancer stem cells during EMT and progression to bone metastasis, Hiraga et al 67 showed that CD44 overexpression in breast, myeloma and prostate cancer cells promotes bone metastasis by enhancing tumourigenicity, cell migration, invasion and production of extracellular matrix haluronan.…”
Section: Intergrinsmentioning
confidence: 58%
“…2 However, it should be noted that expression of CXCR4 is not a universal feature in breast cancer bone homing. We and others have generated bone-homing clones of MDA-MB-231 cells (BO2 and MDA-IV cells) using the same method as described by Kang et al 2,65,66 Interestingly, CXCR4 was not detected in either of these bone-homing cell lines by microarray or PCR analysis.…”
Section: Chemokinesmentioning
confidence: 99%
“…2 Analysis of primary tumour and matched metastases from breast cancer patients show that only tumour cells that are metastatic to the skeleton express proteins of bone origin (cathepsin K, osteonectin, cadherin-11, connexin-43 and Runx2). 46 Prostate cancer bone metastases express the Notch-1 receptor that induces Runx2 expression, a master regulator of osteogenesis also involved in osteomimicry. 47 Bone lesions result in the interaction between cancer cells, bone microenvironment and bone cells themselves.…”
Section: Mirnas Regulate Bone Marrow Invasion and Colonisation By Canmentioning
confidence: 99%